2005
DOI: 10.1177/026119290503300207
|View full text |Cite
|
Sign up to set email alerts
|

Anaesthesia and Post-operative Analgesia following Experimental Surgery in Laboratory Rodents: Are we Making Progress?

Abstract: Current attitudes to the use of animals in biomedical research require that any pain or distress should be minimised. This can often be achieved by the use of appropriate anaesthetic and analgesic regimens. There, is however, little information on the peri-operative regimens used. A literature review was conducted to estimate how commonly analgesics are administered to laboratory rodents, the most widely used species of laboratory animals, and to assess the anaesthetic regimens employed. Studies describing pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
117
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(121 citation statements)
references
References 21 publications
(21 reference statements)
2
117
0
2
Order By: Relevance
“…Mice are also increasingly used in complex investigations requiring additional surgical intervention. Doubtless, post-operative pain relief following surgical procedures such as laparotomy would seem to be necessary, but is often omitted as documented in a recent survey [1]. A reason given for withholding analgesics from laboratory rodents is that no signs of pain were observed and therefore analgesics were considered to be unnecessary.…”
Section: Introductionmentioning
confidence: 99%
“…Mice are also increasingly used in complex investigations requiring additional surgical intervention. Doubtless, post-operative pain relief following surgical procedures such as laparotomy would seem to be necessary, but is often omitted as documented in a recent survey [1]. A reason given for withholding analgesics from laboratory rodents is that no signs of pain were observed and therefore analgesics were considered to be unnecessary.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of pain on experimental results are well described but often neglected; only 20% of papers currently report analgesic treatment (Richardson and Flecknell 2005). Much evidence suggests the identification of pain assessment and treatment as a principle of efficient management.…”
Section: Refinement and Reduction As Tools To Achieve Better Resultsmentioning
confidence: 99%
“…Twenty-six of 34 articles gaining an AAUI of 5 did so by not reporting antimicrobial use when antimicrobials were not recommended. In studies analysing the reported versus actual use of analgesic drugs in laboratory animals, follow-up interviews with corresponding authors revealed that reported analgesic use closely corresponded with the actuality (Richardson and Flecknell 2005). If the same is true in this review then a tendency to good practice is revealed.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study examining analgesic use in laboratory animals found little difference between the reported and actual administration frequency of analgesics when the latter were determined by contacting corresponding authors (Richardson and Flecknell 2005). On this basis, it is assumed that reported and actual levels of antimicrobial use are similar.…”
Section: Discussionmentioning
confidence: 99%